Role of vagus nerve stimulation in epilepsy - Kmak, Bożena (Quality in Sport, 2024)
Introduction and purpose: Epilepsy affects 1% globally, with 2.6 to 6 million cases in Europe. 30-40% of the 50 million epilepsy patients globally don’t respond to drugs. For those ineligible for surgery, Vagus Nerve Stimulation (VNS) therapy offers an alternative for drug-resistant epilepsy and major depression. A brief description of the state of knowledge: Vagus Nerve Stimulation (VNS) is a modern therapy using implanted or non-invasive devices to regulate nerve activity with controlled electrical impulses. Vagus Nerve Stimulation (VNS) is effective for focal seizures, including simple partial seizures and auras. It also shows promise in reducing seizures in generalized tonic-clonic seizures and benefits patients with epileptic encephalopathies like Lennox-Gastaut syndrome. VNS effectively decreases both the frequency and duration of seizures in individuals contending with intractable epilepsy. The use of vagus nerve stimulation is generally a safe and well-tolerated form of treatment. VNS therapy improves psychomotor functions in patients with severe drug-resistant epilepsy, showing positive effects on cognitive aspects. The precise mechanism through which VNS affects the body is not fully understood, but it has demonstrated effectiveness, especially in cases of drug-resistant epilepsy. Conclusions: Extensive research backs Vagus Nerve Stimulation (VNS) as an effective palliative for intractable epilepsy, reducing seizures. Yet, identifying specific patients who would benefit most from VNS treatment lacks clear criteria. Neuromodulation remains crucial for healthcare professionals handling drug-resistant epilepsy.